Ekspresi Seni dalam Islam Kajian atas Pemikiran Ismail Raji Al-Faruqi - Pinem, Masmedia (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
This paper tries to explain the monotheism and artistic expression in Islam which is offered by al-Faruqi. This study focuses on the monotheism as themain objectives of the Islamic worldview. Furthermore, the aesthetic and artistic expression is part of the monotheism that aimsÃ‚Â to take societies or humankind to aware of the transcendent ideas. The idea of monotheism is an expression of the beautiful values (idea ofÃ‚Â beauty) which is objective, transcendent, mystical, and inexpressible, and the idea of beauty (idea of beautifulness) that are subjective, expressive, and cultural understanding. The thought of al-Faruqi shows that literary arts, calligraphy, ornaments, music, and the art of space are inseparable from the monotheism as the Islamic worldview.